The Contribution of Agricultural Marketing Co-operative Societies to Farmers’ Livelihoods in Mvomero and Kilombero Districts, Tanzania - Anderson RWELA (Journal of Oasis Agriculture and Sustainable Development, 2023)
Collective action through Agricultural Marketing Co-operative Societies (AMCOS) is a significant tool for improving smallholder livelihoods; hence, contributing to farmers’ economic development. AMCOS provides a favourable atmosphere for an effective government aid scheme, farm input supply, and mobilization of funds from external support services organizations. However, farmers are facing many challenges, such as inadequate access to agricultural credit, market linkage, information, inadequate technologies, and underperforming markets. There are mixed findings on whether or not agricultural cooperatives improve members’ livelihoods. Therefore, this study evaluated the contribution of AMCOS to members’ livelihood outcomes and constraints for sustainable livelihood development. A total of 340 respondents were interviewed. The findings showed that AMCOS members had higher outcomes in some livelihoods than non-members of AMCOS. In addition, AMCOS contributed to members’ income and some of the assets. Lastly, stakeholders pointed out inefficient service delivery, inadequate skills of co-operative managers, and district co-operative officers’ interference in AMCOS business, which deprived members of co-operative autonomy, as constraints facing AMCOS to enhance sustainable livelihoods for members. Therefore, the study recommends that AMCOS management improve service delivery and plan for continuous staff development. Also, District Co-operative Officers should observe co-operative principles and values in executing their duties.